Registro em prontuário: compreensão do processo de ensino aprendizagem no âmbito da Terapia Ocupacional em contextos hospitalares - Bombarda, Tatiana Barbieri (2019)
The medical record, designated as a collective construction derived from multiple specialized registries, shows the assistance procedures performed and aim at improving the quality of attention to the user. In Occupational Therapy, the medical records aim to reflect the professional reasoning and chronologically enable the visualization of the course of the therapeutic intervention and the occupational performance of the patient throughout the care process. Despite the great importance, the record in medical records presents as an unexplored topic in the scientific field of the Brazilian Occupational Therapy. With the objective of identifying and understanding the teaching-learning process of the medical records in the hospital context existing in the undergraduate courses in Occupational Therapy in Brazil, this quantitative-qualitative study was delineated in two stages: a) documentary research - that consisted in the survey and analysis of documents referring to theoretical disciplines and of professional training of hospital contexts offered by undergraduate courses in Occupational Therapy in Brazil, b) field research - application of an online questionnaire with teachers responsible for occupational therapy disciplines in hospital contexts and students in the practice of a vocational training in the hospital. The data obtained were analyzed by descriptive statistics and discourse of the collective subject. As results, it was verified that the analyzed documents do not gift contents that sustain the practice of documentation, however, students and teachers generally signal, to carry out assessment, intervention and discharge records in accordance with the items recommended in legislation. As fragile aspects of the records, the occupational therapeutic diagnosis and the prognosis were identified. It was verified that the process of teaching-learning of the record in the medical record occurs mostly linked to the activities of professional training, which can be problematic when observed the information that not all students practice internship in the hospital field and that there are students who have access only for medical records. The main teaching-learning strategies employed in undergraduate courses were the discussions of clinical cases and supervised practices, with the main difficulties encountered in this process being the difficulty of access to the medical records, coupled with the dynamics of the service and the lack of standardization in the terminology of the profession. It is believed that the low frequency of insertion of information on prognosis in the medical record correlates with the specificities of the hospital field and that the scarce insertion of the occupational therapeutic diagnosis is linked to the absence of national discussion about this elaboration. Regarding the teaching strategies adopted, it is believed that these are aimed at instigating the development of professional reasoning and reflective critical capacity in relation to intervention, a factor that may contribute to the qualification of the medical record, given the better perception of the role of the occupational therapist and his praxis in the hospital. It is concluded that in general there are weaknesses in the teaching-learning process of the record in medical records, a factor that demands investments in the qualification of training for the documentary practice, which will favor better recognition of the profession